Non-small Cell Lung Cancer Cells Modulate the Development of Human CD1c+ Conventional Dendritic Cell Subsets Mediated by CD103 and CD205 - Lu, Yong; Xu, Wenlong; Gu, Yanli; Chang, Xu; Wei, Guojian; Rong, Zhien; Qin, Li; Chen, Xiaoping; Zhou, Fang (Frontiers in Immunology, 2019)
Advanced non-small cell lung cancer (NSCLC) leads to a high death rate in patients and is a major threat to human health. NSCLC induces an immune suppressive microenvironment and escapes from immune surveillance in vivo. At present, the molecular mechanisms of NSCLC immunopathogenesis and the immune suppressive microenvironment induced by NSCLC have not been fully elucidated. Here, we focus on the effect of NSCLC cells on the development and differentiation of human CD1c+ conventional dendritic cells (DC) subsets mediated by CD205 and CD103. The peripheral blood mononuclear cells (PBMCs) were isolated from NSCLC patients and healthy donors. DCs were induced and cocultured with primary NSCLC cells or tumor cell line H1299. DCs without incubation with tumor cells are control. The protein expression of costimulatory molecules such as CD80 and CD86, HLA-DR, pro-/anti-inflammatory cytokines such as IL-10 and IL-12, CD205 and CD103 on CD1c+ DCs was detected by flowcytometry. Our data revealed two new subpopulations of human CD1c+ DCs (CD1c+CD205+CD103+ and CD1c+CD205+CD103- DC) in healthy donors and NSCLC patients. NSCLC cells inhibit the development of the CD1c+CD205+CD103+ DC subset but facilitate the differentiation of the CD1c+CD205+CD103- DC subpopulation in vitro and ex vivo. NSCLC cells also suppress the expression of signal molecules such as CD40, CD80, CD86 and HLA-DR on CD1c+ DCs. In addition, the production of pro-inflammatory cytokines, including IL-12 and IL-23, is downregulated by NSCLC cells; however, the secretion of anti-inflammatory cytokines, such as IL-10 and IL-27, by CD1c+ DCs is upregulated by NSCLC cells. Our results suggest that NSCLC cells may induce immune tolerogenic DCs, which block DC-mediated anti-tumor immunity in NSCLC patients. Our data may be helpful in revealing new cellular mechanisms related to the induction of tolerogenic CD1c+ DCs by NSCLCs and the development of an immune suppressive microenvironment that causes tumor cells to escape immune surveillance. Our results indicate a potential role for CD1c+ DC subsets mediated by CD205 and CD103 in DC-mediated immunotherapy to target NSCLC in the future.